GE_GERICHTE P/555/2013 vom 6. Januar 2015 - GE Cour de justice (2015)
INFRACTIONS CONTRE L'AUTORITÉ PUBLIQUE; RÉSISTANCE; POLICE; INDEMNITÉ(EN GÉNÉRAL); DOMMAGES-INTÉRÊTS; TORT MORAL | CP.286.1; LPol.17.1; LPol.17.2; CPP.429.1.a; CPP.429.1.c; CPP.422.1; CPP.135.2